Deskripsi Keterkaitan antara Pembelajaran IPA terhadap Aspek Sopan Santun - Dwi Cahyaningsih; Eva Suhaeni Marpaung (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study was to describe the relationship between the ability of students in science subjects on aspects manners in SMP Negeri 3 Jambi. The method used in this research is descriptive method, where research is conducted to find out the value of variables independently, either one or more variables without making comparisons, or connecting with other variables. In this study, there were 50 respondents consisting of 25 students of class VII A and 25 students of class VII B. The instrument used was a questionnaire. The results showed that students in the class VII A has politeness in the high category, while students in grade VIII B has a politeness in the low category.